Health Literacy, Self-efficacy, Food Label Use, and Diet in Young Adults - Cha, EunSeok (2014)
OBJECTIVES: Relationships between health literacy, self-efficacy, food label use, and dietary quality in young adults aged 18-29 were examined. METHODS: Health literacy, self-efficacy, food label use, and dietary quality were assessed. Participants were categorized into low, medium and high health literacy groups based on Newest Vital Sign score. RESULTS: Self-efficacy and health literacy were predictors of food label use, which positively predicted dietary quality. The low health literacy group had significantly lower use of food labels than the high health literacy group. However, there was no significant difference between medium and high health literacy groups. CONCLUSION: Strategies to enhance health literacy, self efficacy and food label use should be developed to improve dietary quality and health outcomes.